Integrated perfusion and separation systems for entrainment of insulin secretion from islets of Langerhans. Issue 3 (4th December 2014) - Yi, Lian; Wang, Xue; Dhumpa, Raghuram; Schrell, Adrian M.; Mukhitov, Nikita; Roper, Michael G.
Abstract : A microfluidic system was developed to investigate the entrainment of insulin secretion from islets of Langerhans to oscillatory glucose levels. Abstract : A microfluidic system was developed to investigate the entrainment of insulin secretion from islets of Langerhans to oscillatory glucose levels. A gravity-driven perfusion system was integrated with a microfluidic system to deliver sinusoidal glucose waveforms to the islet chamber. Automated manipulation of the height of the perfusion syringes allowed precise control of the ratio of two perfusion solutions into a chamber containing 1–10 islets. Insulin levels in the perfusate were measured using an online competitive electrophoretic immunoassay with a sampling period of 10 s. The insulin immunoassay had a detection limit of 3 nM with RSDs of calibration points ranging from 2–8%. At 11 mM glucose, insulin secretion from single islets was oscillatory with a period ranging from 3–6 min. Application of a small amplitude sinusoidal wave of glucose with a period of 5 or 10 min, shifted the period of the insulin oscillations to this forcing period. Exposing groups of 6–10 islets to a sinusoidal glucose wave synchronized their behavior, producing a coherent pulsatile insulin response from the population. These results demonstrate the feasibility of the developed system for the study of oscillatory insulin secretion and can be easily modified for investigating the dynamic nature of other hormones released from different cell types.